Translation and a politics of forgiveness in South Africa? : What black Christians believe, and white Christians do not seem to understand - Forster, Dion Angus (Stellenbosch Theological Journal, 2018)
Why would white South Africans want to be forgiven? Is it in order to secure their future, or to escape from their past? Why is it that some black South Africans find forgiveness to be impossible in the current social and political reality? Forgiveness, as a theological and social discourse in South Africa, is deeply contested. This research shows that black and white South Africans understand notions, and processes of forgiveness in very different ways. This is a significant problem that is compounded by the legacy of ongoing structural injustice as a result of Apartheid. Un-reconciled persons in South Africa seldom have contact with each other since the apartheid system separated persons racially, according to economic class and geographically. In at least one sense this makes a shared understanding of, and approach to, forgiveness impossible. To some extent, South Africans do not truly encounter one another in meaningful engagement, or in spaces of shared meaning. In other words, there is both a hermeneutic and a social barrier to forgiveness in South Africa. Paul Ricoeur's notion of translation can help to engage the complexities that exist in language and the very nature of the difference between the self and the other in what is termed a "politics of forgiveness".